Higher Education in Innovation Ecosystems - Cai, Yuzhuo; Ma, Jinyuan; Chen, Qiongqiong (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Higher education has been considered both an 'engine' for innovation and a 'catalyst' for sustainability development; the integration of both the innovation engine and sustainability catalyst roles are discussed in a recently published Special Issue on the theme of Higher Education in Innovation Ecosystems in the journal Sustainability. Based on 16 articles contributing to the Special Issue from various perspectives, the Special Issue editors have developed an overarching framework about the relationships between higher education and innovation ecosystems. In the framework, we re-define the concept of innovation ecosystem and identify emerging roles of universities in developing sustainable innovation ecosystems. Re-conceptualization of innovation ecosystems In the editorial of the Special Issue, innovation ecosystem is defined as: co-innovation networks in which actors from organizations concerned with the functions of knowledge production, wealth creation, and norm control interact with each other in forming co-evolution and interdependent relations (both direct or indirect) in cross-geographical contexts and through which new ideas and approaches from various internal and external sources are integrated into a platform to generate shared values for the sustainable transformation of society. Compared with most commonly cited definitions of innovation ecosystem, our definition highlights three new aspects of interactions in co-innovation networks: cross-sectoral, transnational, and indirect, drawing insights from the literature including innovation, geography, and biology studies. The roles of universities in innovation ecosystems The emerging roles of universities in innovation ecosystems are as follows: (1) The role of universities is changing from being a central player in technology transfer to being an anchor in knowledge exchange; (2) universities are assuming a new role in trust-building between actors in innovation ecosystems; and (3) universities are not merely an entrepreneurial universities but are also institutional entrepreneur in the innovation ecosystem. The three emerging roles all indicate that universities are becoming the catalysts for sustainable development in innovation ecosystems. Knowledge exchange is crucial for sustainability; trust is the foundation of the sustainable networks; social entrepreneurship is indispensable for sustainable social change. Evidence in wider contexts A total of 44 authors from 10 countries contributed to the discussions on the changing roles of higher education in innovation ecosystems from varying perspectives. They also report transformations within higher education and universities' responses to both external and internal transformations. When addressing these issues, the studies provide both theoretical and methodological contributions to the research on higher education in innovation ecosystems. The 16 articles can be generally placed into four categories: (1) new demands for universities arising from the transformation in society toward innovation ecosystems, (2) transformations within higher education responding to emerging societal demands, (3) dynamics of the interaction of university with other innovation actors in a transnational context, and (4) academic and student mobility for higher education innovation. Calling for a new research agenda While societal changes demand broader roles of universities, they also call for and leads to substantial changes within the internal fabric of the university. The innovations in both society and the universities necessitate a renewed understanding of higher education in society, which has become a new research agenda in studies on innovation in higher education. We hope our Special Issue will inspire and encourage more scholars to join the research field.